The Art of Southern Arabian Daggers: An Emblem of Pride Masculinity and Identity - Khadeeja Althagafi (Arts, 2022)
The long-held tradition of wearing daggers in southern Arabia is in decline. This research examines the rich history of the southern Arabian dagger, outlining its story over time, craftsmanship, and changing use, from a weapon to a ceremonial piece. A significant contribution in the field of visual art is offered, firstly by demonstrating the beauty of this metal artwork form, and secondly by examining the notions of pride, masculinity and identity with regard to southern Arabian dagger wearing. It is argued here that men in this region continue to attach meaning to the dagger. Additionally, existing critical studies, including the various efforts being made to respect and preserve the dagger’s cultural significance, are highlighted. It is contended here that for these reasons, the southern Arabian dagger will not be lost to history.